Evaluation of Phytochemicals and In Vitro Anticancer Activity of Eupatorium Triplinerve - G., Suja; Kumar T., Vinoth; P., Suganya (International Journal of Scientific Research in Biological Sciences, 2019)
The present study attempts to evaluate the phytochemical activity and in vitro anticancer activity of Eupatorium triplinerve methanol extract against lung cancer cell line A-549 and normal cell line Vero. The compound was analyzed for the presence of various phytoconstituents and screened for its cytotoxicity at five different concentrations by MTT assay. The phytochemical profile exhibited the presence of alkaloids, phenolics, flavonoids and steroids. The study documented that the percentage of cell viability has been reduced with the increased concentration, as evidenced by cell death. Eupatorium triplinerve extract shows potential cytotoxic activity with CTC50 of 450 µg/ml and 110 µg/ml against A-549 and Vero cell line respectively. The result obtained was comparably potent, the crude extract showed moderate activity against cancer cells and it was less toxic to the normal cells. In future, research need to be explored in the purification of this extract and identification of lead compound which could be used as a therapeutic tool against lung cancer